Style Musik Tradisional Nias Pada Keyboard Dalam Mengiringi Lagu Buku Zinunö 261 Ya’e Zumange Di BNKP Tarutung Kota - Yerlin For Wance Lombu; Testi Bazarni Zebua; Aprinaldi Simarangkir; Eben Heazarni Telaumbanua; Boho Parulian Pardede (LPPM Politeknik Pratama, 2023)
The aim of this research is to find out how to accompany the lyrics of the song Ya'e Zumange, including keyboard playing style, meter patterns and rhyme patterns and to find out the musical structure used in the song Ya'e Zumange. The song Ya'e Zumange has the theme Zumange (offerings) and this song is a praise song sung when collecting offerings at worship at BNKP Tarutung city. This research uses a qualitative research method using instruments, interview research, documentation, literature study and observation. The author chose the song Ya'e Zumange which has the basic tone D=DO Bar 4/4 with a tempo of M, M 62-68 (Andante) which consists of 8 bars, there are two phrases. The motifs are a, b, c. by using types of language styles, namely mesodiplosis, anaphora and apophasi and the tempo in completing one verse of the song Ya'e Zumange and has low ambitus, the highest pitch and the song structure is monophonic.